Molecular Engineering of Ion-Conducting Polymers for Fuel Cell Membrane Applications. (14th September 2015) - Lee, Woo-Hyung; Mohanty, Angela D; Bae, Chulsung
Abstract : Aromatic polymers functionalized with various sulfonate groups and ammonium cations were synthesized for use in proton exchange membranes (PEMs) and anion exchange membranes (AEMs), respectively. The effect of these different ionic side groups of polymers on membrane transport properties will be discussed. On second part, high-molecular-weight quaternary ammonium (QA)-tethered aromatic polymers that are void of alkaline labile C–O bonds were prepared to achieve improved stability of AEM fuel cells. This new class of hydrocarbon polymers showed high hydroxide ion conductivity and excellent alkaline stability at 80 °C. Overall, this work provides a new synthetic strategy for preparation of AEMs with good fuel cell performance and excellent stability.